Effects of oral salt supplementation on physical performance during a half-ironman: A randomized controlled trial - Del Coso, J.; Gonzalez-Millan, C.; Salinero, J. J.; Abian-Vicen, J.; Areces, F.; Lledo, M.; Lara, B.; Gallo-Salazar, C.; Ruiz-Vicente, D. (Scandinavian Journal of Medicine & Science in Sports, 2016)
The aim of this study was to investigate the effectiveness of oral salt supplementation to improve exercise performance during a half-ironman triathlon. Twenty-six experienced triathletes were matched for age, anthropometric data, and training status, and randomly placed into the salt group (113 mmol Na+ and 112 mmol Cl-) or the control group (cellulose). The experimental treatments were ingested before and during a real half-ironman triathlon competition. Pre- and post-race body mass, maximal force during a whole-body isometric strength test, maximal height during a countermovement jump, were measured, and blood samples were obtained. Sweat samples were obtained during the running section. Total race time was lower in the salt group than in the control group (P = 0.04). After the race, whole-body isometric strength (P = 0.17) and jump height (P = 0.49) were similarly reduced in both groups. Sweat loss (P = 0.98) and sweat Na+ concentration (P = 0.72) were similar between groups. However, body mass tended to be less reduced in the salt group than in the control group (P = 0.09) while post-race serum Na+ (P = 0.03) and Cl- (P = 0.03) concentrations were higher in the salt group than in the control group. Oral salt supplementation was effective to lessen body mass loss and increase serum electrolyte concentration during a real half-ironman